Unprecedented Demonstration of Regioselective SEAr Reaction giving Unsymmetrical Regioregular Oligothiophenes. Issue 19 (24th March 2016) - Moussallem, Chady; Olivier, Simon; Grolleau, Jérémie; Allain, Magali; Mallet, Charlotte; Savitha, Gurunathan; Gohier, Frédéric; Frère, Pierre
Abstract: Aromatization of 4‐cyano‐3‐oxotetrahydrothiophene by sulfuryl chloride gives the new building block 4‐cyano‐3‐pyrrolidylthiophene, which forms unsymmetrical regioregular oligothiophenes with a strict alternation of the donor and acceptor groups along the conjugated system. The self‐coupling reactions that form the oligomers are shown to proceed by a regioselective electrophilic aromatic substitution mechanism involving a stabilized Wheland intermediate. Abstract : First alternate : Regioregular oligothiophenes based on the 3‐pyrrolidyl‐4‐cyanothiophene building block, with a strict alternation of the donor and acceptor groups along the conjugated backbone, have been prepared in one step. The mechanism of formation of the oligomers corresponds to a regioselective self‐electrophilic aromatic substitution (self‐SE Ar) involving a stabilized Wheland intermediate.